Bai’inah menurut Imam Syafi’i dan Relevansinya dengan Akad Perbankan Syariah - Abdul Tri Wanza; Nasri Hamang; Rusnaena (BANCO: Jurnal Manajemen dan Perbankan Syariah, 2022)
Bai'inah is a sale and purchase transaction carried out by a trader with a buyer at a price that has been determined firmly and then the goods are re-sold to sales at a price lower than the first price in cash. Bai'inah is still not fully allowed in the process of buying and selling transactions. There are still many scholars who do not allow the buying and selling of Inah, one of them is Imam Malik. As for those who allow Bai'inah, namely Imam Shafi'i because selling Inah has fulfilled the pillars and conditions in the transaction. This study works to determine the understanding of the Imam Shafi'i school of Bai'Inah and its relevance to Islamic banking contracts. The type of research used is library research that uses data analysis, searches for theoretical books and journals as author's reference material in accordance with the guidelines for writing scientific papers published by IAIN Parepare and don't forget to study other research methods so that relevant research can be found. . The results of this study indicate that Imam Syafi'i allowed Bai'inah because it had fulfilled the terms and conditions in the sale and purchase transaction. The relevance of the Bai'inah contract used in this transaction is the service of Islamic banking products with the use of murabahah contract products and gold-based financing in financial institutions. which affects people using Bai'inah contracts, namely by making it easier for people to get funds from property financing for the desired goods with an agreement that in the future the customer can resell it with payment in cash, which has been agreed between the bank and the customer..